Adolescent Stress, AI and Social Media: Clinical and Educational Perspectives for 2025 - Sava, Nicu-Ionel; Popa, Brigitte; Dolea, Mihaela (New Trends in Psychology, 2025)
This article explores the psychological impact of stress in adolescents, with a particular focus on the role of artificial intelligence (AI) and social media as amplifiers of emotional vulnerability. The aim is to identify clinical risk factors, outline evidence-based interventions, and offer recommendations for educational and mental health professionals. Building on recent studies in developmental psychology and digital well-being (Haidt, 2023; Valkenburg & Nesi, 2022), this paper integrates clinical and educational perspectives to bridge gaps between research and practice in adolescent mental health. The article employs an integrative literature review methodology, synthesizing findings from psychological, sociological, and neurodevelopmental research, combined with case studies from educational and clinical settings. The synthesis highlights that excessive exposure to social media, algorithm-driven content, and online comparison processes are strongly associated with increased anxiety, depression, and body image concerns among adolescents. These findings emphasize the urgent need for mental health screening in schools, digital literacy programs, and early therapeutic interventions tailored to adolescents’ developmental needs. The paper contributes a timely and interdisciplinary perspective on adolescent stress, integrating AI-related challenges and proposing concrete recommendations for educators, clinicians, and policymakers.